RISK ASSESSMENT IN PROJECT PLANNING USING FMEA AND CRITICAL PATH METHOD - Sandra Milena CHOLES ARVILLA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
This paper is based upon the research undertaken for the development of the doctoral thesis “Management of software projects based on object-oriented technology”. The study examines the existing risk management practices commonly used for classic software development. The goal is to integrate the elements of the traditional risk management methodologies to create a new agile risk management methodology. The thesis focuses on techniques that can be easily implemented in extreme programming (XP) and SCRUM. This study is motivated by the following research questions: What are the elements of existing quality assurance tools that could meet the principles of agile development? And is it possible to use risk estimation for improving quality in agile projects? The thesis presents a synthesis of the most common risk management techniques, as well as an introduction to agile methods XP and SCRUM. The proposal integrates the concepts of Failure Mode and Effect Analysis into the iterative life cycle of an agile software project. The thesis presents a metamodel which integrates the concepts of agile development methodologies: SCRUM and XP with the FMEA concepts for risk quantification. The model was partly implemented into a real development project. Partial results show the improvement in early identification of failures and allowed to reconsider the Sprint plan.